Considerations for a sustainable hybrid mini-grid system: A case for Wanale village, Uganda - Kimera, Raymond; Okou, Richard; Sebitosi, Adoniya Ben; Awodele, Kehinde O. (Journal of Energy in Southern Africa, 2014)
The extension of modern energy services to rural sub-Saharan Africa has continuously provided a challenge to energy utilities. The continued reliance on diesel generators for rural electrification is increasingly becoming unsustainable, due to a number of factors, among which includes their high fuel dependency, and the uncertainty surrounding the price and availability of fossil fuels. While the influx of renewable energy technologies has provided a means for providing off-grid electrification services, the intermittent nature of renewable resources poses a challenge, as energy generation does not always coincide with usage. Through a combination of renewable energy technologies, energy storage, and conventional diesel generation, a hybrid mini-grid system is able to achieve synergy in operation, hence providing a reliable means of extending electricity services to rural consumers. In this paper, a hybrid mini-grid system is proposed for the supply of electricity to a remote village in Uganda. Renewable energy resources are identified, an estimation of the projected village short-term electricity demand is modelled, and using HOMER software, a hybrid mini-grid system is designed, components sized, and the system optimized for efficient and reliable operation to meet the village demand at an affordable cost. A well designed and operated hybrid mini-grid system offers a viable tool for the electrification of even the remotest of areas.